Respiratory failure in a diabetic ketoacidosis patient with severe hypophosphatemia - Han Saem Choi; Ahreum Kwon; Hyun Wook Chae; Junghwan Suh; Duk Hee Kim; Ho-Seong Kim (Korean Society of Pediatric Endocrinology, 2018)
Phosphate is essential in regulating human metabolic processes, and severe hypophosphatemia can induce neurologic and hematological complications and result in respiratory failure and cardiac dysfunction. Therefore, correction of severe hypophosphatemia can be pivotal in the management of diabetic ketoacidosis (DKA). We report the case of a 14-year-old female who was diagnosed with type 1 diabetes and referred to our institute for treatment of DKA. Although the patient received fluid and continuous insulin administration according to the current DKA treatment protocol, generalized tonic seizures and cardiac arrest developed. After cardiopulmonary resuscitation, the patient recovered and was stable. Within 16 hours after DKA treatment, the patient developed respiratory failure with severe hypophosphatemia that required mechanical ventilation. Concurrent neurologic evaluation revealed no specific abnormalities. The patient recovered without any complications after correcting the hypophosphatemia. We suggest vigilant monitoring of the phosphate level in DKA patients and active replacement when required.